Effect of Net Profit Margin and Company Size on Risk Disclosure - Fatmawatie, Naning; Natalina, Sri Anugerah; Fauza, Hasna (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
Net Profit Margin is part of the profitability ratio, which is a ratio to assess the company's ability to seek profit. Company size is a value that shows the size of the company. Both of these factors have a relationship with risk disclosure. This study aims to determine the Net Profit Margin, Company Size, Risk Disclosure, and the effect of Net Profit Margin and Company Size on Risk Disclosure in Property and Real Estate Companies. Registered with the ISSI 2016-2018 period. This study uses a quantitative approach. The data used is secondary data, analyzed using correlation analysis and multiple linear regression. The sample in this study amounted to 84 annual financial reports. The results showed that Net Profit Margin, Company Size, and Risk Disclosure were in the poor, suitable, and adequate categories, respectively. The partial calculation results show that the Net Profit Margin has no effect on Risk Disclosure, but Company Size affects Risk Disclosure. Meanwhile, the simultaneous calculation results show that Net Profit Margin and Company Size have a significant effect on Risk Disclosure with a value of 13.6%, while other factors explain the remaining 86.4% outside of this study, such as the ratio leverage, liquidity ratios, and product or industry diversification.